Correlation study between clinical special tests for myelopathy and static MRI parameters in patients of Malaysian population treated for cervical dysfunction - Zakaria@Mohamad, Zamzuri; Sharifudin, Mohd Ariff; Din, Hishamudin; Abd. Aziz, Azian; Karupiah, Rajandra Kumar (Cureus, Inc., 2021)
Introduction: Cervical spondylotic myelopathy (CSM) is the most common cause of spinal cord dysfunction. Magnetic resonance imaging (MRI) remains the imaging modality of choice, but its findings are not completely specific for clinically significant CSM. This cross-sectional study aims to determine the pathoanatomy of CSM in patients and analyze the correlations between clinical key symptoms, myelopathic signs, and MRI findings. Methods: Patients with CSM aged 30 to 80 years old with no previous cervical spine disease or injuries were recruited. Clinical parameters include myelopathic hand signs and other clinical-specific tests. The MRI findings were analyzed for level of compression, underlying degenerative pathology, and parameters for cord compression. Results: Thirty patients were recruited. The most common myelopathic signs observed were positive Hoffmann’s sign and the presence of reverse brachioradialis reflex. All patients had either degenerative or prolapse disc changes on MRI. There was a positive correlation between the clinical key features with MRI parameters for canal and cord diameter. The transverse cord diameter, cord compression ratio, and approximate cord area were the only independent variables related to almost all the positive clinical specific tests. All three have a moderate to strong correlation with the clinical findings. Conclusion: The MRI parameters such as canal and cord size of the cervical spine are an objective reflection of compression on the spinal cord. Correlations observed indicate cord compression that plays a major role in the pathophysiology of CSM. These measurements are sensitive indicators of canal stenosis and play a significant role in predicting the severity and outcome of CSM.